PRELIMINARY STUDY OF A IMAGE ANALYSIS SETUP APPROACH OF THERMAL TRACING JET ENGINE PARTS USING THERMAL PAINTS - S.R. Ghulam; M. Chandel (INTERNATIONAL JOURNAL ENGINEERING AND APPLIED TECHNOLOGY (IJEAT), 2020)
Reduced engine performance comes with a higher operating temperature, and that limit is imposed by component material life. It is critical to have an accurate, full-field evaluation of the metal temperature of the hot section components for engine designers to develop dependable and lasting engines. Using conventional thermometry isn't recommended since it fails to generate heat gradients and results in problems when transferring data from measurement sites to the readout unit. It has recently been discovered that the thermal transfer condition has changed, and as a result, the actual temperature of the components cannot be measured. A paint will permanently change color if it is exposed to heat, this kind of paint is known as a temperature signaling paint. The traditional method is to test the thermal coatings personally. A manual process of interpretation results in mistakes because there is no accurate detection of isothermal limits that impact human eyesight. A systematic methodology for automated interpretation of thermal paints is detailed in this paper. A technique for orderly picture capture, image segmentation, and image processing, which employs a correct algorithm for surface temperature interpretation, has been addressed.